Pengalaman Kepenuhan Roh Kudus dalam Perspektif Epistemologi Pentakostalisme - Junifrius Gultom; David E.S. Korengkeng (EPIGRAPHE: Jurnal Teologi dan Pelayanan Kristiani, 2023)
The experience of the fullness of the Holy Spirit by speaking in tongues and its implementation in spiritual life activities is a matter of debate to this day. The pneumatological epistemology of Pentecostalism would be able to answer the need for dogmatic understanding in building a theological epistemology that changes every person in their life activities. The purpose of this paper is a biblical study of the fullness of the Holy Spirit explicitly speaking in tongues which will provide a philosophical and theological foundation in the Pentecostal epistemology perspective. The research method used was descriptive qualitative. The research results show that the experience of the fullness of the Holy Spirit in the Pentecostal tradition is considered a real manifestation of the divine presence. Participants in this study reported transformative experiences that included spiritual ecstasy, increased spiritual awareness, and receipt of spiritual gifts. Additionally, these experiences also influence their understanding of religious truth and lead to a deeper commitment to active religious practice. The epistemological perspective of Pentecostalism recognizes that religious knowledge is not only cognitive but also comes from deep spiritual experience. The experience of the fullness of the Holy Spirit is considered a valid source of knowledge and has the same authority as academic theology. Therefore, spiritual experience is the main basis for forming the beliefs and worldview of Pentecostal believers.